Un cas exemplaire de prophylaxie de la délinquance juvénile : le traitement médico-pédagogique de l’enfant subnormal placé à l’École de préservation Théophile Roussel de Montesson - Dominique Messineo (Criminocorpus)
The article aims to return to the main operating principles of the Montesson preservation house since its refoundation in 1902. Succeeding to an agricultural penal colony, the new preservation house-Théophile Roussel presents itself as a model institution highlighting implements such as a mental orthopedic program (strict hygiene, ambitious professional education program, careful selection of residents judged on the basis of their psychological characteristics as being the most reformable) in order to prevent the dangers of juvenile crime. From this moment, correctional education is partly absorbed in the wake of medicine and psychological care. The article presents the shift in meaning which then takes place in the reform of juvenile justice by privileging references to the medical practices and speeches of doctors such as Thulié, Magnan, Legrain, and Boncour in order to build a medico-educational treatment of phenomena that generate delinquency among minors identified in the subnormal character of children mainly placed by their families.